2022
DOI: 10.1590/1519-6984.267996
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic pollutants are associated with reproductive alterations and genotoxicity in estuarine fish (Sciades herzbergii - Bloch, 1794) from the Amazon Equatorial Coast

Abstract: Estuaries are constantly subject to continuous environmental impacts of human activities, such as fisheries, port or industry, and domestic sewage, with fish being one of the most affected aquatic animals, reflecting the impacts directly on their bodies. Thus, the aim of this study was to carry out the biomonitoring of an estuary located on the Amazonian Equatorial Coast through analysis of PAHs (Polycyclic Aromatic Hydrocarbons) in the water, in addition to trace metals, histopathological alterations and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The presence of contaminants in the aquatic environment can influence the health of organisms present there, causing various damages to tissues (Noleto et al, 2022;Freitas et al, 2022). Next, we will highlight the morphological changes found in gill and liver tissues of S. herzbergii.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of contaminants in the aquatic environment can influence the health of organisms present there, causing various damages to tissues (Noleto et al, 2022;Freitas et al, 2022). Next, we will highlight the morphological changes found in gill and liver tissues of S. herzbergii.…”
Section: Discussionmentioning
confidence: 98%
“…These authors add that this reduction in the size of fish in the São Marcos area may be associated with the high levels of turbidity found, in addition to the presence of contaminants. Noleto et al (2022) when analyzing muscle samples from 68 specimens of S. herzbergii collected in São José Bay (São José de Ribamar), identified concentrations of trace elements (lead, zinc, iron and magnesium) above the limits recommended by Brazilian legislation for fish meat, indicating that the analyzed fish are suffering some level of environmental contamination. Pinheiro-Sousa et al (2021) identified trace elements and polycyclic aromatic hydrocarbons (PAHs) in sediments in the same region as the present study.…”
Section: Discussionmentioning
confidence: 99%